Advances in global leadership. Vol. 5 - Mobley, William H.; Wang, Ying; Li, Ming (Advances in global leadership,, 2009)
The urgency of a deeper understanding of the nature and development of leaders who can be effective across multiple contexts and national boundaries has never been more apparent. The Advances in Global Leadership Series seeks to contribute to this understanding by presenting original papers by academics, practitioners and consultants actively engaged in global leadership from multiple perspectives. Volume 5 of this series includes chapters on: personality, leadership and globalization; the roles of international experience, experiential learning, and cultural intelligence in developing global leaders; an integrative framework for assessing, coaching and developing global leaders; developing balanced global leadership teams; leadership in strategic alliances; leadership in the Mid-East, Korea and Europe; leadership and environmental scanning; and, ethical leadership. Authors of this title come from China, Ireland, Korea, Singapore, U.K. and USA.